Ca(v)1.3 and deafness - Lee, Amy (Henry Stewart Talks, 2012)
Auditory transmission, Voltage-gated Ca(v) Ca2+ channels, Role of Ca(v)1.3 in auditory hair cells, How alterations in Ca(v)1.3 may cause deafness